Sinularin Selectively Kills Breast Cancer Cells Showing G2/M Arrest, Apoptosis, and Oxidative DNA Damage - Huang, Hurng-Wern; Tang, Jen-Yang; Ou-Yang, Fu; Wang, Hui-Ru; Guan, Pei-Ying; Huang, Chiung-Yao; Chen, Chung-Yi; Hou, Ming-Feng; Sheu, Jyh-Horng; Chang, Hsueh-Wei (Molecules (Basel, Switzerland), 2018)
The natural compound sinularin, isolated from marine soft corals, is antiproliferative against several cancers, but its possible selective killing effect has rarely been investigated. This study investigates the selective killing potential and mechanisms of sinularin-treated breast cancer cells. In 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H- tetrazolium, inner salt (MTS) assay, sinularin dose-responsively decreased the cell viability of two breast cancer (SKBR3 and MDA-MB-231) cells, but showed less effect on breast normal (M10) cells after a 24 h treatment. According to 7-aminoactinomycin D (7AAD) flow cytometry, sinularin dose-responsively induced the G2/M cycle arrest of SKBR3 cells. Sinularin dose-responsively induced apoptosis on SKBR3 cells in terms of a flow cytometry-based annexin V/7AAD assay and pancaspase activity, as well as Western blotting for cleaved forms of poly(ADP-ribose) polymerase (PARP), caspases 3, 8, and 9. These caspases and PARP activations were suppressed by N-acetylcysteine (NAC) pretreatment. Moreover, sinularin dose-responsively induced oxidative stress and DNA damage according to flow cytometry analyses of reactive oxygen species (ROS), mitochondrial membrane potential (MitoMP), mitochondrial superoxide, and 8-oxo-2′-deoxyguanosine (8-oxodG)). In conclusion, sinularin induces selective killing, G2/M arrest, apoptosis, and oxidative DNA damage of breast cancer cells.